THE NATURAL ATOMIC ORBITAL POINT-CHARGE MODEL FOR PM3 - MULTIPOLE MOMENTS AND MOLECULAR ELECTROSTATIC POTENTIALS - Beck, Bernd; Rauhut, Guntram; Clark, Timothy (Journal of Computational Chemistry, 1994)
The natural atomic orbital/point (NAG-PC) model originally developed to calculate molecular electrostatic potentials (MEPs) and multiple moments based on the AM1 wave function has been extended to PM3. As for AM1, NAO-PC/PMS reproduces dipole moments calculated by the standard PM3 method very well. There is also a surprisingly good correlation between experimental and calculated quadrupole moments. The MEPs calculated using PM3/NAO-PC are found to be in better agreement with those given by RHF/6-31G* than those obtained from the PM3 wave function using Coulson charges. On the other hand, the NAG-PC model is often slightly worse then the method implemented in MOPAC-ESP. The MEPs calculated using our model based on the PM3 wave function are often in better agreement with those given by RHF/6-31G* than those obtain with AM1. (C) 1994 by John Wiley and Sons, Inc.